Integer Programming Formulation of Constrained Reliability Problems - Tillman, F. A.; Liittschwager, J. M. (Management Science, 1967)
This paper investigates the solution by integer programming of reliability optimization problems which are subject to linear and nonlinear separable restraints. In particular, the following problems are solved: (1) maximizing reliability for a parallel redundancy system subject to multiple linear restraints, (2) minimizing cost of a parallel redundancy system subject to multiple nonlinear and separable restraint functions while maintaining an acceptable level of reliability, (3) optimal choice of design for a parallel redundancy system. Also discussed are the necessary alterations to the above formulations for problems involving standby redundant units.